Room temperature quantum spin Hall states in two-dimensional crystals composed of pentagonal rings and their quantum wells - Ma, Yandong; Kou, Liangzhi; Li, Xiao; Dai, Ying; Heine, Thomas (NPG Asia Materials, 2016)
Quantum spin Hall (QSH) insulators are a peculiar phase of matter exhibiting excellent quantum transport properties with potential applications in lower-power-consuming electronic devices. Currently, among all predicted or synthesized QSH insulators, square and hexagonal atomic rings are the dominant structural motifs, and QSH insulators composed of pentagonal rings have not yet been reported. Here, based on first-principles calculations, we predict a family of large-gap QSH insulators in SnX2 (X=S, Se, or Te) two-dimensional (2D) crystals by the direct calculation of Z2 topological invariants and edge states. Remarkably, in contrast to all known QSH insulators, the QSH insulators predicted here are composed entirely of pentagonal rings. Moreover, these systems can produce sizeable nontrivial gaps ranging from 121 to 224 meV, which is sufficiently large for practical applications at room temperature. Additionally, we propose a quantum well by sandwiching an SnTe2 2D crystal between two BiOBiS2 sheets and reveal that the considered 2D crystal remains topologically nontrivial with a sizeable gap. This finding demonstrates the robustness of its band topology against the effect of the substrate and provides a viable method for further experimental studies.
CRIS-Team Scopus Importer:2023-03-20